PENGEMBANGAN E-LKPD TERINTEGRASI VIRTUAL LAB PHET INTERACTIVE SIMULATION PADA PEMBELAJARAN IPAS KELAS IV SEKOLAH DASAR - Bunga Okta Ramadona; Muhammad Sofwan; Risdalina Risdalina (EDUTECH : Jurnal Inovasi Pendidikan Berbantuan Teknologi, 2026)
This study aims to Develop an Electronic Student Worksheet (E-LKPD) built on the Liveworksheets platform and integrated with the PhET Interactive Simulation virtual lab as an instructional medium for Natural and Social Sciences (IPAS) learning on the topic of Energy and Its Transformation for fourth-grade elementary school students. The study was motivated by the limited availability of interactive and contextual digital learning media, which has contributed to low student engagement and insufficient conceptual understanding in IPAS learning. This study employed a Research and Development (R&D) method, which is a research approach used to produce a specific product while simultaneously testing its feasibility and effectiveness. Product Development followed the DDD-E model (Decide, Design, Develop, Evaluate). Data collection instruments included expert validation sheets and student response questionnaires. Validation results showed that the E-LKPD received feasibility scores of 95,45% from the media expert, 87.71% from the subject matter expert, and 98% from the language expert, all of which fall within the "highly feasible" category. The small-group trial yielded a score of 85,20%, while the large-group trial yielded 90,27%, both categorised as "very good". Accordingly, the Liveworksheets-based E-LKPD integrated with the PhET Interactive Simulation virtual lab on the topic of Energy and Its Transformation is deemed feasible and effective for use as an IPAS instructional medium in fourth-grade elementary school classrooms. ABSTRAKPenelitian ini bertujuan untuk mengembangkan Elektronik Lembar Kerja Peserta Didik (E-LKPD) berbasis website Liveworksheets yang terintegrasi dengan virtual lab PhET Interactive Simulation sebagai media pembelajaran Ilmu Pengetahuan Alam dan Sosial (IPAS) pada materi Energi dan Perubahannya bagi peserta didik kelas IV Sekolah Dasar. Latar belakang penelitian ini didasarkan pada kurangnya media pembelajaran digital yang interaktif dan kontekstual, sehingga berdampak pada rendahnya keterlibatan dan pemahaman konsep peserta didik dalam pembelajaran IPAS. Penelitian ini menggunakan metode Research and Development (R&D), yakni metode penelitian yang digunakan untuk menghasilkan produk tertentu sekaligus menguji kelayakan dan keefektifan produk tersebut. Pengembangan produk dilakukan menggunakan model DDD-E (Decide, Design, Develop, Evaluate). Instrumen pengumpulan data meliputi lembar validasi ahli dan angket respons peserta didik. Hasil validasi menunjukkan bahwa E-LKPD yang dikembangkan memperoleh skor kelayakan sebesar 95,45% dari ahli media, 85,71% dari ahli materi, dan 98,66% dari ahli bahasa, yang seluruhnya masuk dalam kategori "sangat layak". Hasil uji coba kelompok kecil memperoleh skor sebesar 87,20% dan uji coba kelompok besar sebesar 90,27%, keduanya berada pada kategori "sangat baik". Dengan demikian, E-LKPD berbasis Liveworksheets yang terintegrasi virtual lab PhET Interactive Simulation pada materi Energi dan Perubahannya dinyatakan layak dan efektif digunakan sebagai media pembelajaran IPAS di kelas IV Sekolah Dasar.